(untitled) (Fiep Bulletin - online, 2013)
The history of mankind shows us a taste in that man in general is the alcoholic beverage. Since when are more preferred than the others, for its tonic effect and euforizante to alleviate the anguish and to release what is repressed. Much of the polução, regardless of sex, believes his "performance" or "good physical performance" has its cause in the intake of alcohol. The use of alcoholic beverages is as old as humanity itself. Drinking moderate and occasionally is part of the habits of various companies. Determining the borderline between the social drinking, or using abusive or harmful use of alcohol and alcoholism (syndrome of dependence on alcohol) are sometimes difficult because these limits are thin, vary from person to person and from culture to culture. The SDA or alcoholism (alcohol dependence syndrome) is today a disease with physical and social consequences more damaging, "which takes the individual problems to develop biological, social or psychological." This article presents some complications about the excessive use of alcohol and the benefits of physical activity as auxiliary treatment, no drug, the recovery of bodies affected by the use of alcohol. Identifying himself as a new proposal for rehabilitation of people affected by this pathology. The aim is also to open a more in-depth research on issues that permeate this study.